The relationship between service quality of vegetable contract farming in Selangor towards farmers satisfaction in FAMA / Siti Norhaslinda Ibrahim - Ibrahim, Siti Norhaslinda (Faculty of Business and Management, 2007)
Based on the first chapter, the researcher can concluded that FAMA is the government body that are doing marketing program to all entrepreneurs that have potential product but have lack of knowledge on how to market it. Besides that, contract farming is one program that encourages people to get involved in farming program. FAMA will provide them with money, training and fertilizer. Sometimes problems will occur when conducting it such as inefficient management, marketing problems and monopoly position. Research objective of this study is to determine the level of service quality of contract farming and effectiveness towards their users that are the farmers. This research is also beneficial to FAMA itself, farmers and the researcher. For the second chapter, researcher search information on satisfaction, quality, service quality and model for analysis that is suitable to this research. The importance of customer satisfaction for a firm's long-term business survival and growth, monitoring customer satisfaction and diagnosing what factors drive customers' satisfaction should be an essential activity of every firm. While for quality, it is sometimes viewed in relation to some idea of a standard. Excellence-based definitions proposed the idea that products or services may include elements that are perceived as superior or even transcendental. Moreover, Hansen (2001, p. 2005) defines quality as value and then writes that value as the relation between price and quality. One of the most widely used instruments to measure service quality is the SERVQUAL scale developed by Parasuraman in 1985, which then being refined in 1988 and 1991. The model on which SERVQUAL is proposed that customers evaluate the quality of a service on five distinct dimensions are reliability, responsiveness, assurance, empathy and tangibles. Besides that, for research methodology that is suitable to use. Descriptive research is used in order to determine the farmers satisfaction level of service quality provided by FAMA. While unit of analysis refers to the farmers that are doing vegetable contract, farming and only 60 respondents are selected randomly as a sampling frame. The actual populations of farmers that are doing vegetable contract farming are 76. The researcher collects the data from primary sources through questionnaire that based on the Likert scale method. Furthermore, for data analysis, researcher use the SPSS software to compiled and calculated the data. Researcher calculates the data by using reliability test, Pearson correlation coefficient, t-test, ANOVA and others.